Exotic states of nuclear matter : proceedings of the International Symposium EXOCT07, Catania University, Italy, 11-15 June 2007 - Lombardo, Umberto (World Scientific, 2008)
The International Symposium on "Exotic States of Nuclear Matter" was a unique opportunity to review and discuss the many aspects of nuclear matter under extreme conditions and the corresponding possible exotic states like hyperonic matter, kaon condensates, and quark matter, which can appear both in astrophysical compact objects like neutron stars and in heavy ion collision experiments. In this proceedings volume, leading experts from astrophysics, nuclear physics, and elementary particle physics have delivered reviews and specialized seminars, which highlight the links among the different fields and the role of the underlying fundamental processes. Prospects in future astrophysical observations, with present and planned apparata, and heavy ion experiments are strongly emphasized. Thus, this book will definitely be a valuable reference for all researchers working in this wide research area.